Cylindrical wormgearings with progressively curved shape of teeth flanks - Hlebanja, Gorazd (Strojniški vestnik, 2009)
A wormgearing or a worm gear set, featuring concavely shaped worm contact flanks and convex worm gear teeth is proposed in this paper. Corresponding flank profiles are defined by a mathematical function enabling progressive curvatures of profiles. This function is used to define a basic worm profile in the axial plane, wherefrom worm flank surface and mating worm gear profile and flank surface are derived. Furthermore, cutting tools for manufacturing such wormgearing are defined. Kinematic circumstances are discussed in detail,thus disclosing the emergence of contact lines (surfaces). The essential characteristics of the proposed wormgearing are that its entire teeth flank surfaces in contact are involved in power transmission and that concave-convex contacts exist anywhere on flank surfaces. Thus, improved properties in power transmission and lubrication can be expected, consequentlyresulting in lower energy losses and lower wear.
Keywords: prenos moči; zobniki; polžasti zodbniki